Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha) - Perez, Thierry; Ruiz, Cesar (Zootaxa, 2018)
The sponge class Homoscleromorpha has a challenging taxonomy and its systematics is still a matter of debate. A significant effort has recently been deployed to better evaluate the diversity of these sponges, and each new exploration of cryptic habitats reveals new species. Although several undescribed or wrongly determined Oscarella-like sponges have been reported by different authors, the Oscarellidae family still lacks description of its true Caribbean representatives. The exploration of various submarine caves in the Lesser Antilles has allowed us to find and to formally describe the first two Oscarellidae of the Caribbean Sea, Oscarella filipoi sp. nov. and Oscarella zoranja sp. nov. Both new species are quite common in semi-dark habitats throughout the Lesser Antilles. Moreover, O. filipoi sp. nov. is the largest Oscarellidae ever observed world-wide. Both species harbor a sylleibid aquiferous system and a high density of ovoid to spherical choanocyte chambers. The molecular taxonomy clearly shows their affiliation to the Oscarella clade containing the type species of the Oscarellidae family. In addition to their growth forms, these two species differ in the shape of their mesohylar cells, and in the degree of development of their basal region. This latter trait is particularly remarkable in large specimens of O. filipoi which can have a very thick ectosome.